Metal‐Free Synthesis of Thermally Stable Fluorescent p‐Terphenyls by Ring Transformation of 2H‐Pyran‐2‐ones. Issue 25 (2nd July 2020) - Chandrasekar, Subashini; Singh, Fateh V.
Abstract: A metal‐free approach for the synthesis of p ‐terphenyls 7  a –i and cyclic p ‐terphenyls 9  a –d and 11  a –d is described via carbanion induced ring transformation reaction of 6‐biphenyl‐2 H ‐pyran‐2‐ones 5 with malononitrile 6, cyclohexanone 8 and 1, 4‐cyclohexanedione monoethylene ketal 10 respectively. Additionally, the base‐mediated ring transformation reactions were working smoothly under mild reaction conditions and ring transformation products 7, 9 and 11 were isolated in good to excellent yields. The synthetic approach provides the flexibility of introducing of both electron‐withdrawing and ‐donating functionalities in p ‐terphenyl architecture. Moreover, the photo physical properties of compounds 7, 9 and 11 were analyzed using UV‐visible and Fluorescence Spectroscopy. p ‐Terphenyls 7  c showed cyan fluorescence in chloroform (λmax (em): 508 nm) and acetonitrile (λmax (em): 420 nm) while cyclic p ‐terphenyl 9  a showed blue fluorescence in chloroform and 1, 4‐dioxane (λmax (em): 470 nm). Similarly, compound 11  a showed blue fluorescence in chloroform (λmax (em): 468 nm) and 1, 4‐dioxane (λmax (em): 473 nm). Additionally, the thermal stability of synthesized cyclic p ‐terphenyls 11  a, 11  c and 11  d were also studied using TG and DTA techniques. Abstract : A simple and convenient route for the synthesis of cyclic and acyclic para ‐terphenyls was described through carbanion‐induced ring transformation of 2 H ‐pyran‐2‐ones under mild reaction conditions. The potential of the method lies in generating p ‐terphenyls functionalized with different electron donating and withdrawing functionalities in terphenyls architecture. Moreover, the photo‐physical behaviour of synthesized p ‐terphenyls was studied using UV‐visible and Fluorescence Spectroscopy. Additionally, the thermal stability of cyclic p ‐terphenyls was also studied using TG and DTA techniques.